Sofosbuvir: a novel oral agent for chronic hepatitis C - Cholongitas, Evangelos (Hellenic Society of Gastroenterology, 2014)
Major changes have emerged during the last few years in the therapy of patients with chronic hepatitis C (CHC). Several direct acting antiviral agents (DAAs) have been developed showing potent activity against hepatitis C virus (HCV) and incrementally improving the rates of sustained virological response (SVR), even in difficult-to-treat CHC patients. Sofosbuvir, a new nucleotide analog, HCV NS5B polymerase inhibitor, represents the first key step towards the new era in the management of CHC, since it is the first approved DAA with excellent tolerability and favorable pharmacokinetic profile, limited potential for drug interactions, potent antiviral activity and high genetic barrier against all HCV genotypes. Sofosbuvir has recently become commercially available in combination with ribavirin, with or without pegylated interferon, achieving high SVR rates after 12-24 weeks of therapy. Finally, since interferon-free regimens are close to becoming the new standard of care in CHC patients, sofosbuvir has an ideal profile to be the cornerstone antiviral agent, especially in difficult-to-treat CHC patients, given in combination with other new DAAs. This review summarizes the main updated issues related to the efficacy and safety of sofosbuvir-containing regimens in CHC patients.